2016
DOI: 10.1056/nejmoa1512913
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes of Surgical Treatment of Severe Ischemic Mitral Regurgitation

Abstract: BACKGROUND In a randomized trial comparing mitral-valve repair with mitral-valve replacement in patients with severe ischemic mitral regurgitation, we found no significant difference in the left ventricular end-systolic volume index (LVESVI), survival, or adverse events at 1 year after surgery. However, patients in the repair group had significantly more recurrences of moderate or severe mitral regurgitation. We now report the 2-year out-comes of this trial. METHODS We randomly assigned 251 patients to mitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
587
9
25

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 800 publications
(643 citation statements)
references
References 44 publications
22
587
9
25
Order By: Relevance
“…This is similar to the prevalence reported after surgical MV repair, and is a predictor of increased mortality and cardiac complications (6,7). As with surgical mitral restrictive annuloplasty, the Cardioband reduced the septolateral diameter of the mitral annulus (3.67±0.47 vs. 2.41±0.44 cm, P<0.001), but did not address the coexisting geometric subvalvular distortions.…”
supporting
confidence: 73%
“…This is similar to the prevalence reported after surgical MV repair, and is a predictor of increased mortality and cardiac complications (6,7). As with surgical mitral restrictive annuloplasty, the Cardioband reduced the septolateral diameter of the mitral annulus (3.67±0.47 vs. 2.41±0.44 cm, P<0.001), but did not address the coexisting geometric subvalvular distortions.…”
supporting
confidence: 73%
“…Given the high rate of recurrent mitral regurgitation in patients after RA-repair, surgeons have to consider chordalsparing mitral-valve replacement or combined procedure with subvalvular repair and undersizing mitral annuloplasty to solve ischemic mitral disorder (9)(10)(11)(12)(13)(14). The results of the two-years randomized trial in patients with moderate and severe IMR by the Cardiothoracic Surgical Trials Network (CTSN) imposed the need to revise the surgical dogma regarding the superiority of mitral valve repair over replacement (9,10).…”
Section: Specific Surgical Perspectives In Imrmentioning
confidence: 99%
“…The results of the two-years randomized trial in patients with moderate and severe IMR by the Cardiothoracic Surgical Trials Network (CTSN) imposed the need to revise the surgical dogma regarding the superiority of mitral valve repair over replacement (9,10). Moreover, we reported the results of a randomized study in patients with severe IMR who received a combined procedure of subvalvular repair [papillary muscle approximation, (PMA)] and undersizing mitral annuloplasty compared to restrictive annuloplasty alone.…”
Section: Specific Surgical Perspectives In Imrmentioning
confidence: 99%
“…Due to the progressive nature of the underlying ventricular disease recurrence, an FMR is common after mitral valve repair. 16 The European Heart Survey showed that up to 50% of patients with severe symptomatic MR are not referred for surgery due to advanced age, other comorbidities, and operative risk. 4 Patients with severe MR who are not offered surgery due to high operative risk (STS risk score .12 and logistic EuroScore .20) and are medically treated have a 50% mortality at 5 years.…”
Section: Corrective Interventions For Mitral Regurgitationmentioning
confidence: 99%